Fibre optic dosimetry in synchrotron microbeam radiation therapy. (January 2019) - Archer, J; Li, E; Rosenfeld, A B; Lerch, M
Abstract: Synchrotron microbeam radiation therapy is a novel pre-clinical therapy method that uses high brilliance, spatially fractionated, low energy x-rays to deliver a very high dose rate. A conventional spatial fractionation for these beams is 50 μm microbeam width at 400 μm peak-to-peak separation. To perform dosimetry on these beams, a dosimeter with a high spatial resolution is required. We present a plastic scintillator fibre optic dosimeter that has been demonstrated to be able to resolve the microbeam structure. The advantages of such a dosimeter is the water equivalence, passive components exposed to the radiation field, relatively inexpensive components and simple fabrication. We use cylindrical BC-400 plastic scintillator optically coupled to a 1 mm diameter core plastic optical fibre. BC-620 reflective paint was coated on the end of the probe to maximise the capture of light. A silicon photomultiplier (SensL MiniSM) was used to measure the light output of the probe. A 50 μm resolution probe and 20 μm probe was tested at the Australian Synchrotron, on the Imaging and Medical Beam-Line. We were able to resolve microbeams with both resolution probes. The depth dose measurements matched that of a Pinpoint ionisation chamber except for an over-response at shallow depth.